Management of giant hepatic cysts in the laparoscopic era - Chan Joong Choi; Young Hoon Kim; Young Hoon Roh; Ghap Joong Jung; Jeong Wook Seo; Yang Hyun Baek; Sung Wook Lee; Myung Hwan Roh; San Young Han; Jin Sook Jeong (Annals of surgical treatment and research, 2013)
Purpose: We sought to evaluate the feasibility and outcomes of laparoscopic resection of giant hepatic cysts and surgical success, focusing on cyst recurrence. Methods: From February 2004 to August 2011, 37 consecutive patients with symptomatic hepatic cysts were evaluated and treated at Dong-A University Hospital. Indications were simple cysts (n = 20), multiple cysts (n = 6), polycystic disease (n =2), and cystadenoma (n = 9). Results: The median patient age was 64 years, with a mean lesion diameter of 11.4cm. The coincidence between preoperative imaging and final pathologic diagnosis was 54% and half (n = 19) of the cysts were located in segments VII and VIII. Twenty-two patients had American Society of Anesthesiologists (ASA) classification I and II, and nine had ASA classification III. Surgical treatment of hepatic cysts were open liver resection (n = 3), laparoscopic deroofing (n = 24), laparoscopic cyst excision (n = 4), laparoscopic left lateral sectionectomy (n = 2), hand assisted laparoscopic procedure (n = 2), and single port laparoscopic deroofing (n = 2). The mean fellow-up was 21 months, and six patients (16%) experienced radiographicapparent recurrence. Reoperation due to recurrence was performed in two patients. Among the factors predicting recurrence, multivariate analysis revealed that interventional radiological procedures and pathologic diagnosis were statistically significant. Conclusion: Laparoscopic resection of giant hepatic cysts is a simple and effective method to relieve symptoms with minimal surgical trauma. Moreover, the recurrence is dependent on the type of pathology involved, and the sclerotherapy undertaken. Purpose: We sought to evaluate the feasibility and outcomes of laparoscopic resection of giant hepatic cysts and surgical success, focusing on cyst recurrence. Methods: From February 2004 to August 2011, 37 consecutive patients with symptomatic hepatic cysts were evaluated and treated at Dong-A University Hospital. Indications were simple cysts (n = 20), multiple cysts (n = 6), polycystic disease (n =2), and cystadenoma (n = 9). Results: The median patient age was 64 years, with a mean lesion diameter of 11.4cm. The coincidence between preoperative imaging and final pathologic diagnosis was 54% and half (n = 19) of the cysts were located in segments VII and VIII. Twenty-two patients had American Society of Anesthesiologists (ASA) classification I and II, and nine had ASA classification III. Surgical treatment of hepatic cysts were open liver resection (n = 3), laparoscopic deroofing (n = 24), laparoscopic cyst excision (n = 4), laparoscopic left lateral sectionectomy (n = 2), hand assisted laparoscopic procedure (n = 2), and single port laparoscopic deroofing (n = 2). The mean fellow-up was 21 months, and six patients (16%) experienced radiographicapparent recurrence. Reoperation due to recurrence was performed in two patients. KCI Citation Count: 2